2020
DOI: 10.5304/jafscd.2020.101.027
|View full text |Cite
|
Sign up to set email alerts
|

Making seafood accessible to low-income and nutritionally vulnerable populations on the U.S. West Coast

Abstract: Along the U.S. West Coast, sustainable manage­ment has rebuilt fish stocks, providing an oppor­tunity to supply nutrient-rich food to adjacent coastal communities where food insecurity and diet-based diseases are common. However, the market has not successfully supplied locally sourced seafood to nutritionally vulnerable people. Rather, a few organizations make this connection on a limited scale. We used a “positive deviant” approach to learn how these organizations’ efforts developed, how they overcame challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Fish-meat substitutability has not been widely studied, but the possibility of replacing meats with blue foods or plant-based alternatives seems to be an attractive policy option 35,72 . Strategies to achieve these goals could include combining soft policy tools such as dietary guidelines or behavioural nudging to mainstream eating and cooking blue foods 76,77 , with harder regulatory interventions and economic disincentives for high-carbon-emissions food [78][79][80][81] .…”
Section: Human Health and Environmental Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Fish-meat substitutability has not been widely studied, but the possibility of replacing meats with blue foods or plant-based alternatives seems to be an attractive policy option 35,72 . Strategies to achieve these goals could include combining soft policy tools such as dietary guidelines or behavioural nudging to mainstream eating and cooking blue foods 76,77 , with harder regulatory interventions and economic disincentives for high-carbon-emissions food [78][79][80][81] .…”
Section: Human Health and Environmental Sustainabilitymentioning
confidence: 99%
“…The combination of species and productions systems that provide most resilience to a changing climate will be highly context specific, yet the species that offer opportunities for efficiencies and bulk production under a changing climate (such as tilapia with a high temperature tolerance range) may not be the most culturally appropriate or nutrient-dense aquatic foods 1 . Navigating this apparent trade-off could involve complementing bulk production of fewer species with environmentally sustainable cultivation and capture of a diversity of species that provide additional nutrition (for example, dried fish powder) and more inclusive supply chains 77 .…”
Section: Navigating Trade-offsmentioning
confidence: 99%
“…Another model‐based study indicated a nationwide programme to improve small‐scale production in Bangladesh would increase vitamin A intakes and save thousands of lives, and could be implemented more cheaply than a national wheat flour fortification programme, with similar aims (Fiedler et al, 2016). On the U.S. West Coast, a number of non‐profit organizations and for‐profit fish distribution businesses have found novel approaches to overcome obstacles to distribute fish to low‐income communities, for example, sending affordable fish to nearby schools (Koehn et al, 2020). While specific programmatic interventions show impressive results, and industry advertising stresses the healthfulness of aquatic foods, there are few examples of nutrition‐sensitive national fisheries policies (Koehn et al, 2017; Thilsted et al, 2016).…”
Section: Introductionmentioning
confidence: 99%